ANALYSIS OF ROOT CANAL PREPARATION DESIGN FOR POST - CROWN RESTORATION AT MAXILLARY CENTRAL INCISOR TOOTH USING FINITE ELEMENT METHOD - JUSUF (NIM : 23606007); Tim Pembimbing : Dr. Ichsan Setya Putra; Dr. Tatacipta Dirgantara; Ga, ANNISA
The purpose of this study was to evaluate stress distributions of endodontically treated maxillary central incisors restored with two combinations of post-core material, which are Cu-Zn post-core with acrylic crowns and composite post-core with ceramic crowns when three different types of root canal designs were incorporated. Three-dimensional finite element computational analysis was performed. Three maxillary incisors models with different types of root canal preparation designs (seat, non-seat and ferrule designs) were simulated. The zinc phosphate cement and BIS GMA resin, adhesive between post-core, crown and root were modeled using spring element at every contact nodes. An arbitrary load of 110 N was applied at 135 o angle with tooth longitudinal axis on the palatal surface of the crown. Von Mises (equivalent stresses) energetic criterion was chosen. Finite element method simulations shows that ferrule design is design that has the smallest maximum stress if its compared with seat and nonseat design. In another case, the most preferable material to used on core wedge is fiber glass material The results of the present study would allow clinicians to make an informed choice and improvement from among available types of root canal preparation designs, to restore endodontically treated teeth.